Comparison of clinicopathological characteristics among adult patients with early and delayed lupus nephritis - Anmol; Tabassum Elahi; Anusha Kumari; Amara Naseer (Journal of the Pakistan Medical Association, 2026)
Objective: To assess clinicopathological characteristics in adult patients with early and delayed lupus nephritis. Method: The comparative, cross-sectional study was conducted at the Department of Nephrology, Sindh Institute of Urology and Transplantation, Karachi, from January to June 2025, and comprised patients of either gender aged 18-50 years with biopsy-proven lupus nephritis. The patients were classified into early lupus nephritis group ELN (<1 year after systemic lupus erythematosus diagnosis) and delayed lupus nephritis group DLN (>1 year after the diagnosis). Baseline demographic, clinical, laboratory, serological and renal biopsy data was collected from all the patients. Histopathology was evaluated as per the International Society of Nephrology / Renal Pathology Society classification by using modified National Institutes of Health activity and chronicity indices. Data was analysed using SPSS 22. Results: Of the 39 patients with mean age 32.6±8.4 years, 33(84.6%) were females. There were 22(56.4%) patients in group ELN and 17(43.6%) in group DLN. Delayed lupus nephritis was associated with a longer duration of systemic lupus erythematosus before renal involvement (p<0.001), higher frequency of hypertension (p=0.04), oliguria (p=0.04) and nephritic syndrome (p=0.04). Patients with delayed lupus nephritis also had higher serum creatinine (p=0.01), lower estimated glomerular filtration rate (p=0.02) and more frequent moderate-to-severe interstitial fibrosis and tubular atrophy (p=0.01) compared to those with early lupus nephritis. Conclusion: Delayed lupus nephritis was associated with more severe renal dysfunction and greater chronic histopathological damage compared to those with early lupus nephritis. Key Words: Chronicity index, Kidney diseases, Lupus nephritis, Systemic lupus erythematosus, Timing of diagnosis.